Analysis of Parameters Affecting the Wheels Lifespan (Current Problems in Rail Vehicles, 2025)
The paper analyses the influences that affect the wear / degradation of the wheel tread profile and thus its lifespan. Up to now, this issue has been mostly viewed in a partial way only. For example, only from the perspective of the geometry of the tread profile, sometimes only from the perspective of the wheel steel grade. This paper, on the other hand, try to summarise all influences acting on the wheel tread profile and thus provide the base for creating predictive model of railway wheel lifespan in various operating conditions.
Keywords: railway wheel; wearing; wheel steel grade; tread profile; LCC